Uma contribui??o ao estudo da qualidade da energia el?trica no suprimento de sistemas de telecomunica??es - Souza, Wagner Camis?o (2002)
The conditions of the availability of electric power in this country are not comfortable. From a technical point of view the solution is to increase system efficiency by reducing losses wherever they may be. This study aims a form of contribution to the task of adjusting the profile of the more significant loads to match this reality. Telecom loads may be heavy, and even though equipment consumption is being reduced with the technology advance, the total installed load is increasing, due to the growth of the existing net and the addition of new ones built by newcomer telecom companies. Within those installations, the main concern is load non-linearity, rather than equipment consumption itself. In fact, most of power in telephone stations are concentrated in the rectifiers, which impose considerable levels of harmonic distortion to the power supply lines, corresponding to a significant portion of system losses. This work presents general concepts on Electric Power Quality, describes the 200 kVA range power supply configuration as recommended by the Telebras Standards, and also evaluates the main performance parameters for the types of rectifiers more likely to behave according to Telebras? six-pulse converter recommendation. Those configurations are able to reduce power lines harmonic distortion and at the same time, comply with all other Standards items.